Factors affecting the space utilisation rate of Malaysian public universities - Abdul Rahman, Mohd. Shahril (Penerbit UTM Press, 2015)
This paper shares the factors that affect space utilization rate in the Malaysian public higher education institutions. The factors, which gathered through a qualitative study involving academics and practitioners are, people, place and process. This helps the Malaysian public universities to understand what they can afford to put forward in order to achieve higher space utilization. Besides, academics and practitioners are encouraged to explore how space utilization can be embraced as a tool in managing space, especially for public higher education institutionsina developing countryy such as Malaysia